Adult attention deficit hyperactivity disorder in patients on methadone maintenance therapy / Sharon Kaur Bhart - Sharon Kaur, Bhart (2018)
BACKGROUND There is a lack of local research regarding the prevalence of adult Attention Deficit Hyperactivity Disorder (ADHD) in patients on Methadone Maintenance Therapy (MMT). Given that current studies report a high prevalence of adult ADHD in these patients along with associated adverse outcomes, it would be useful to determine the factors associated with ADHD in patients on MMT and its impact on substance use related factors. OBJECTIVE This study primarily aims to determine the prevalence of adult ADHD in patients enrolled in the MMT program. In addition, it also aims to determine the association between ADHD and sociodemographic characteristics, substance use related factors, other psychiatric comorbidites, crime, HIV risk and quality of life in patients on MMT. METHODS This is a cross-sectional study conducted in the methadone clinic in Hospital Kuala Lumpur and Klinik Kesihatan Kuala Lumpur. A total of 145 patients with ADHD whose diagnosis were based on the M.I.N.I International Neuropsychiatric Interview-Plus (M.I.N.I.-Plus) (Adult ADHD version) were recruited. Substance use related factors, crime and HIV risk-taking behaviour were assessed with the Opiate Treatment Index (OTI). The presence of other psychiatric comorbidities was assessed using the M.I.N.I and M.I.N.I Plus. Finally, quality of life was assessed using the World Health Organisation Quality of Life BREF (WHOQOL-BREF). vii RESULTS The prevalence of adult ADHD in patients on MMT in this study was 19.3%. A diagnosis of ADHD in these patients was significantly associated with a lower education level and with unemployment. ADHD was also significantly associated with an early age of first drug use, an increase in the number of drugs used and also preferential use of heroin, cannabis and methamphetamines. These patients had a higher number of other psychiatric comorbidities and significantly higher prevalence of Major Depressive Disorder. Patients with comorbid ADHD had higher crime rates, a higher risk of acquiring HIV along with lower quality of life scores. These outcomes remained significant after accounting for a history of conduct disorder. CONCLUSION This study showed a substantial prevalence of adult ADHD in patients on MMT. A diagnosis of ADHD in these patients was associated with unfavourable outcomes in comparison to patients without ADHD. There is a need for the recognition and treatment of adult ADHD in patients enrolled in MMT.